1984
DOI: 10.3109/08923978409026460
|View full text |Cite
|
Sign up to set email alerts
|

Increased Numbers of Suppressor-Cytotoxic Cells in a Patient with Carbamazepine Hypersensitivity

Abstract: A patient is presented with a clinical syndrome of erythroderma, fever, liver function abnormalities, eosinophilia and atypical lymphocytosis due to carbamazepine hypersensitivity. Immunological analysis of peripheral blood mononuclear cells was performed using mouse monoclonal antibodies against T-cell and Ia antigens. A 12-fold increase in the absolute numbers of suppressor-cytotoxic T-cells was found, resulting in a reversed helper/suppressor ratio. Also the number of Ia-positive cells was greatly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This last feature is in agreement with the finding of an increased percentage of circulating helper/inducer T cells by other authors (Boissier et al 1983;Paladini & Marinig 1984). In contrast, Blijham et al (1984) reported an increase in suppressor/cytotoxic T cells in a patient with carbamazepine hypersensitivity. Sinnige et al (1990) reported a case of carbamazepine-associated pseudolymphoma in a 78-yearold woman treated with carbamazepine 200 mg/ day for 6 months, who was initially diagnosed as having a T immunoblastic non-Hodgkin's lymphoma, high grade malignant.…”
Section: Carbamazepinementioning
confidence: 81%
See 2 more Smart Citations
“…This last feature is in agreement with the finding of an increased percentage of circulating helper/inducer T cells by other authors (Boissier et al 1983;Paladini & Marinig 1984). In contrast, Blijham et al (1984) reported an increase in suppressor/cytotoxic T cells in a patient with carbamazepine hypersensitivity. Sinnige et al (1990) reported a case of carbamazepine-associated pseudolymphoma in a 78-yearold woman treated with carbamazepine 200 mg/ day for 6 months, who was initially diagnosed as having a T immunoblastic non-Hodgkin's lymphoma, high grade malignant.…”
Section: Carbamazepinementioning
confidence: 81%
“…Finally, as with phenytoin, there are a few cases of erythroderma and lymphadenopathy in carbamazepine recipients, which may be associated with hypogammaglobulinaemia (Blijham et al 1984;Boissier et al 1983;Gaulier et al 1980). …”
Section: Carbamazepinementioning
confidence: 96%
See 1 more Smart Citation
“…Carbamazepine (Tegretol) is used in the management of seizures, trigeminal neuralgia, and chronic pain syndromes (1,2). The drug has been associated with the induction of a hypersensitivity syndrome consisting of fever, rash, lymphadenopathy, atypical circulating lymphocytes, eosinophilia and elevated liver function tests (3,4). Blijham, reported a patient who in addition to the hypersensitivity syndrome exhibited a reversible proliferation of the T suppressor subset of lymphocytes (4).…”
mentioning
confidence: 99%
“…The drug has been associated with the induction of a hypersensitivity syndrome consisting of fever, rash, lymphadenopathy, atypical circulating lymphocytes, eosinophilia and elevated liver function tests (3,4). Blijham, reported a patient who in addition to the hypersensitivity syndrome exhibited a reversible proliferation of the T suppressor subset of lymphocytes (4). Other adverse reactions to carbamazepine include bone marrow suppression, hepatic and renal dysfunction, water intoxication, and ocular lens opacities (5).…”
mentioning
confidence: 99%